Effects of crude flavonoids from tatary buckwheat on alloxan-induced oxidative stress in mice (Bangladesh Journal of Pharmacology, 2012)
The present study was undertaken to evaluate the effects of crude flavonoids from tatary buckwheat (FTB) on alloxan-induced oxidative stress in mice. After induction of diabetes, diabetic mice were randomly divided into four groups: one diabetic control group and three different doses of FTB (100, 200 and 400 mg/kg) treated groups, with non-diabetic mice used as the normal control group. The mice were intragastrically administered once daily for 28 days. Fasting blood glucose (FBG), serum insulin, superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and malondialdehyde (MDA) were measured. The results showed that FTB could significantly reduce FBG levels and MDA contents, and increase serum insulin levels, SOD, GPx and CAT activities. These data suggested that FTB possess hypoglycemic effects and could reduce alloxan-induced oxidative stress in mice. Therefore, FTB might be of use as an antidiabetic drug.